Nowe studia modernistyczne - Mao, Douglas; Walkowitz, Rebecca (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The main task of this article is to describe the new situation of modernist studies at the turn of the 20th century and an attempt to position this description in a broader history of criticism of modernism in art. The transformations in the studies into modernist literature have been characterized here in three aspects: expanding the time frame (going beyond the basic period of modernism from the end of the 19th c. until 1930s), spatial dimension (abandonment of a privileged position of research into West European and American modernism in favour of a transnational perspective) and vertical dimension (connected with the necessity to rethink the relationship high art-low art, and also the influence of mass media upon modernist literature).